The conducive level of learning and living environment of off-campus students: case study UiTM Shah Alam / Prof. Dr. Dasimah Omar … [et al.] - Omar, Dasimah (Research Management Institute (RMI), 2012)
The impact of near-campus students housing, or off-campus students accommodation cannot be ignored by the universities and as well as the community officials. Numerous scholarly studies have highlighted the substantial economic impacts either direct, indirect or induced, and cumulatively the roles of the universities have significantly contributed to the local economies. The issue of the impacts of off-campus student rental housing on neighbourhoods is one that has been of longstanding but increasing concern in Malaysia Statistically, in Malaysia, there was approximately a total of 1.2 - 1.5 million students in 2009. By the year 2015, it is expected that 50 per cent of 18 to 30 year old active population should gain access to university education, amounting to 120,000 yearly. The objectives of the research are to obtain information on the living and learning conditions of off-campus students prevalent in the tertiary institutions in Malaysia and to isolate those factors that may impede the successful learning so that priority can be given to them in subsequent policy implementations and actions by government and the higher education institutions The research will establish a deliberated review on the capability to interact (social empowerment); the accessibility to local institutional and structural context (social inclusion); the resources that facilitate interaction (socio-economic security); and the necessary collective accepted values and norms, such as trust, that enable community building (social cohesion).